1997
DOI: 10.3354/meps152175
|View full text |Cite
|
Sign up to set email alerts
|

Feeding physiology of Cerastoderma edule in response to a wide range of seston concentrations

Abstract: The suspension-feeding activity of Cei-astoderrna edule (L ) was investigated in response to a wide range of experimental seston concentrations which approximated the changes in seston quality and quantity found in the natural environment over tidal cycles of sediment resuspension. The different seston concentrations were produced by adding increasing quantities of resuspended fine sediment to a relatively low and constant algal concentration (0.59 mg dry wt I-'). The total seston concentrations (total particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
92
2
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(102 citation statements)
references
References 29 publications
5
92
2
3
Order By: Relevance
“…A similar dependence of absorption efficiency upon the organic content of ingested particles has been observed in many other species of bivalve shellfish (e.g. Bricelj & Malouf 1984, Bayne , Navarro et al 1993, Barille et al 1997, Navarro & Widdows 1997. Hawkins et al 1998a, suggesting that efficiencies of absorption are primarily limited by digestive processes.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…A similar dependence of absorption efficiency upon the organic content of ingested particles has been observed in many other species of bivalve shellfish (e.g. Bricelj & Malouf 1984, Bayne , Navarro et al 1993, Barille et al 1997, Navarro & Widdows 1997. Hawkins et al 1998a, suggesting that efficiencies of absorption are primarily limited by digestive processes.…”
Section: Discussionsupporting
confidence: 66%
“…Falconer & Owens 1990, Haure 1996. To better understand how filterfeeders function under such turbid conditions, a growing body of work has studied responses to increasing concentrations of natural seston (Sornin et al, 1983, Deslous-Paoli et al 1987, Hawkins et al 1996, Soletchnik et al 1996, Barille et al 1997, Navarro & Widdows 1997. In the present paper, we 0.0 0.5 1.0 1.5 2.0 Chlorophyll a Fig.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Previous studies have shown that as the clearance rate by C. edule gradually declines in response to increasing SPM, the mass filtered and deposited as faeces and pseudofaeces increases with SPM, reaching a maximum at ca 200 mg SPM 1-' (Navarro & Widdows 1997). Consequently, as the SPM increases from low values in the spring/summer to high values in the autumnhinter period, due to the physical/biological interaction (i.e.…”
Section: Biodeposition and Sediment Propertiesmentioning
confidence: 98%
“…The FR of the clam significantly increased in turbidity conditions of up to 750 mg/L. This was a remarkable feat as compared to , and which could filter in turbidity concentrations ranging from 10 to 570 mg/L (Bayne 1993, Navarro & Widdows 1997, Rueda & Smaal 2002 The PP of showed increasing rate at higher TC. Morillo-Manalo and Del Norte-Campos (2010) stated that the production of pseudofaeces implies maximum energy gain for the bivalves during feeding.…”
Section: Methodsmentioning
confidence: 87%